(±)-Salviaprione, a pair of unprecedented abietane-type diterpeniods from Salvia prionitis. Issue 40 (30th September 2015) - Jiang, Yong-Jun; Zhang, Yu; He, Juan; Wu, Xing-De; Shao, Li-Dong; Li, Xiao-Nian; Su, Jia; Peng, Li-Yan; Li, Rong-Tao; Zhao, Qin-Shi
Graphical abstract: Abstract: (+)-Salviaprione and (−)-salviaprione, a pair of unprecedented abietane-type diterpeniods having an unprecedented 5/6/6 tricyclic ring system with a unique five membered ring A formed by a new C-2/C-11 bond, were isolated from the whole plant of Salvia prionitis . The enantiomeric separation was achieved by HPLC on a chiral column. Their structures and absolute configurations were determined on the basis of 1D and 2D NMR spectra, X-ray diffraction, and electronic circular dichroism (ECD). The possible biogenesis for (±)-salviaprione was also postulated.